2015
DOI: 10.1371/journal.pone.0136103
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cell Cycle Regulation in a Natural Equine Model of Asthma

Abstract: Recurrent airway obstruction (RAO) is a common and potentially debilitating lower airway disease in horses, which shares many similarities with human asthma. In susceptible horses RAO exacerbation is caused by environmental allergens and irritants present in hay dust. The objective of this study was the identification of genes and pathways involved in the pathology of RAO by global transcriptome analyses in stimulated peripheral blood mononuclear cells (PBMCs). We performed RNA-seq on PBMCs derived from 40 RAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 119 publications
3
43
0
Order By: Relevance
“…We used a subset of a previously published RNA-seq dataset [50, 56]. Briefly, the 82 samples were derived from three different cohorts of healthy Warmblood horses: one group of horses that were unrelated at the parent level and two half-sibling families.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a subset of a previously published RNA-seq dataset [50, 56]. Briefly, the 82 samples were derived from three different cohorts of healthy Warmblood horses: one group of horses that were unrelated at the parent level and two half-sibling families.…”
Section: Resultsmentioning
confidence: 99%
“…This study is based on the results generated in a previously reported experiment and therefore all methods in detail are described elsewhere [49, 50, 56]. Briefly, blood samples were collected from 41 adult Warmblood horses (free of RAO) from three cohorts: two half-sibling families (Fam1: 7 horses, Fam2: 9 horses) and a group of unrelated horses (Un: 25 horses).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that expression of RAO is not only influenced by environmental factors (mouldy hay) but also by a genetic predisposition . Moreover, it a similar immunological background is suspected, suggesting that some pathophysiological mechanisms, both in RAO and human asthma, are common (Pacholewska et al 2015).…”
mentioning
confidence: 99%